Michael. L Galaty, Lorenc Bejko (eds) Archaeological investigations in a northern Albanian province. Results of the Projekti Arkeologjik i Shkodrës (Memoirs of the Museum of Anthropology 64). Ann Arbor: University of Michigan Press, 2023. Volume 1: Survey - Donev , Damjan (Journal of Greek Archaeology, 2024)
This two-volume monograph presents the results of a multidisciplinary regional archaeological project in the Upper Shkodër Basin, in North Albania. Importantly, PASH, the Albanian acronym for this project, continues the series of regional archaeological projects in Albania, initiated over two decades ago with the Albanian-American collaboration in the hinterlands of Apollonia and Dyrrhachium, the Mallakastra Regional Archaeological Project, or MRAP and the Durrës Regional Archaeological Project, or DRAP. It is all the more pleasing to see the integral results of PASH published in a single, richly illustrated edition and the project data made freely accessible at the Deep Blue data repository. This is entirely in tune with recent calls for data transparency and the need to publish, curate and preserve archaeological datasets.